Study of the structure of hydration products of cement stone with hyperplasticizer and silica microfillers - Abdraimov, I.; Musa, K.; Pukharenko, Yu.; Sailygarayeva, M. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2025)
In this paper, the combined effect of active silica fillers of technogenic and natural origin and polycarboxylate superplasticizer on the structure of the cement matrix was investigated in order to increase its microporosity. It was found that the dispersion of filler particles, the amorphization of the structure and components, are due to the effect of chemical energy on the molecular and surface crystallization structure of binder particles. Studies on the combined introduction of silica and plasticizer in the composition of mortar mixtures make it possible to increase the content of the pozzolanic additive to 15% of the binder weight, which helps to reduce cement consumption, while simultaneously optimizing the microstructure of the cement stone and further obtaining concrete with high construction and technical characteristics. As part of the study, a detailed microstructural study of the cement stone was carried out to analyze the hydration products in the